Preventative stretching and strengthening exercises for the groin on the ATP Tour - Novotny, M. (Medicine and Science in Tennis, 2006)
Tennis players are often affected by groin pain, particularly during the clay court season. The pain may be acute traumatic or overuse in origin. Acute, traumatic groin pain may be caused by a fall, wherein the player has rotated his leg or overextended his adductor muscles. Overuse groin pain involves repetitive contraction of the adductor longus and sometimes the abdominal muscles. The muscle-tendon unit is affected, sometimes in association with increased stress on the inguinal canal, causing pain and tenderness on palpation. There may be degeneration of the involved tendons, with or without micro-ruptures or partial tendon rupture. As with many musculoskeletal injuries, improved strength, flexibility and muscle balance may help prevent groin injury. The preventative training programme described in this article should be started in the off-season and may be continued throughout the competitive season.